Management of ant pests in urban environments (Research, Society and Development, 2023)
Ants (Hymenoptera: Formicidae) are social insects and important pests in the urban environment. The main groups of pest ants in the urban environment are leafcutter and house ants. Leaf-cutter ants cause crescent-shaped defoliation of plants, where in the urban environment it causes problems in gardens and ornamental plants. Domestic ants cause human health problems, contaminate food and cause problems in equipment and buildings. In this work, we propose an integrated ant management program in urban environments. For that, a bibliographic review was carried out addressing the following topics: life cycle of ants, main groups of pest ants, factors that influence their attack, decision-making systems, management strategies and tactics. It is observed that ants are pests that are difficult to control, and successful control is related to the correct execution of the various components of integrated pest management. Regarding control tactics, chemical control is the main method used to control ants in urban environments because the effectiveness of other methods (ie, biological and behavioral control) is poor.